Karakteristik Yoghurt Sinbiotik dengan Penambahan Puree Pisang Mulu Bebe (Musa acuminata) dan Konsentrasi Starter Lactobacillus Bulgaricus yang Berbeda - Umamit, Tirsa; Talebe, Yusnaini B; Lestari, Sri (Cannarium, 2021)
This study aims to determine the interaction between the different concentrations of starter L. bulgaricus and mulu bebe banana puree on the characteristics of sibiotic yogurt, to determine the effect of different L. bulgaricus.This study aims to determine the interaction between the different concentrations of starter L. bulgaricus and mulu bebe banana puree on the characteristics of synbiotic yogurt, to determine the effect of different L. bulgaricusstarter concentrations on the characteristics of synbiotic yogurt, to determine the effect of different mulu bebe bananas on the characteristics of synbiotic yogurt. This research was conducted in September - January 2021. The test is a chemical test. The purpose of this study was to find out the characteristics of yogurt with the addition of banana puree mulu bebe and different concentrations of L. bulgaricus and look at the interaction influence of each - each treatment of banana puree addition and starter concentration with a fermentation duration of 72 hours. This research is an experimental study using complete randomized design (RAL) factorial, the first factor is the concentration of L. bulgaricus and the second factor of banana puree with 16 levels of perlakua and 3 repeats with each starter concentration L. bulgaricus A1 0, A2 2.5, A3 5, A4 7.5, Puree banana B1 0 ml, B2 2 ml, B3 4 ml, B4 6 ml. If there is a difference in influence between the treatment of each factor, then it is continued with Duncan's test. The observed parameters include: rendemen, pH, water content, ash content, and protein content. The results of this study showed banana puree and L. bulgaricus concentration had a real effect (P0.05) on rendemen, ash content, protein content. While the water content has no real effect (P0.05). The interaction between factors A and B in Duncan's advanced test had a significant effect including rendemen, protein levels and ash levels to the characteristics of yogurt.